Screening for adult attention-deficit/hyperactivity disorder in alcohol dependent patients: Underreporting of ADHD symptoms in self-report scales. (1st February 2019) - Luderer, Mathias; Kaplan-Wickel, Nurcihan; Richter, Agnes; Reinhard, Iris; Kiefer, Falk; Weber, Tillmann
Highlights: Validity of the ASRS and CAARS-S-SR were low at the established cut-offs. Only few patients showed positive ADHD screening results at the established cut-offs. Lower thresholds might be needed for adequate ADHD detection rates. Combination of both instruments at lower cut-offs improved psychometric properties. Patients with alcohol dependence under-report ADHD symptoms more than expected. Abstract: Background: Attention-deficit/hyperactivity disorder (ADHD) is a common comorbid disorder that is frequently overlooked in adults with alcohol use disorder (AUD). Moreover, identifying ADHD in AUD patients is time-consuming and difficult. The aim of this study was to assess the clinical utility of two self-report screening instruments for adult ADHD in AUD patients. Methods: 404 adults seeking residential treatment for AUD were screened using the Conners' Adult ADHD Rating Scale Screening Self-Rating (CAARS-S-SR) and the Adult ADHD Rating Scale (ASRS). Results were compared with ADHD diagnosis obtained from a stepped approach: first, a structured interview (Diagnostic Interview for ADHD in adults 2.0.; DIVA) was applied; second, probable ADHD diagnoses had to be confirmed by two expert clinicians. Results: At the previously reported cut-off values, ASRS and CAARS-S-SR showed low sensitivities of 57.1 and 70.6%. A high number of false negative results (NPV ASRS: 89.5%; CAARS-S-SR: 92.3%) indicates underreporting of ADHD symptoms. Sensitivity improved at lower cut-off (ASRS ≥ 11; CAARS-S-SR ≥60) or with a combination of both instruments at lower cut-offs. Area Under the Curve (AUC) for the combination of ASRS and CAARS-S-SR was superior to the AUCs of the single questionnaires. Conclusions: Underreporting of ADHD symptoms in ASRS and CAARS-S-SR of AUD patients requires lower cut-off values to detect the majority of ADHD, albeit at the expense of an increased rate of false-positive results. Cut-off values should be adjusted to the clinical setting. Clinicians should take into consideration that a negative screening result does not necessarily imply absence of ADHD.